2019
DOI: 10.3390/tropicalmed4010014
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Pathogens: An In-Depth Analysis of the Vectorial Potential of Cockroaches

Abstract: Nosocomial or healthcare-associated infections are regarded as the most frequent adverse event that threatens patients’ safety and has serious economic and social consequences. Cockroach infestation is common in many hospitals, especially in the developing world. Common nosocomial pathogens isolated from cockroaches include Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, and Klebsiella pneumoniae. Cockroaches also harbor epidemiologically significant antibiotic-resistant organisms, such as car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 69 publications
3
38
0
1
Order By: Relevance
“…These isolates are known to be major causes of the invasive fungal infections particularly in transplant and Acquired immunode ciency syndrome (AIDS) patients (25)(26). The presence of other known causes of opportunistic and nosocomial fungal infections species such as Cladosporium, Mucor, Fusarium , Rhizopus and Pencillum , further cements the concept that cockroaches in hospitals a may be major public health concern and con rm the ndings of other studies conducted on domestic and hospital cockroaches (1)(2)(3)(4)(5)(6)(7)(8)(9) . What the study ndings indicate is that there needs to be more studies to be conducted to ascertain if medically important fungi on the surfaces of hospital cockroaches are etiological agents of HAIs including of newer fungal pathogens immunocompromised patients such as Talaromyces marneffei (29).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…These isolates are known to be major causes of the invasive fungal infections particularly in transplant and Acquired immunode ciency syndrome (AIDS) patients (25)(26). The presence of other known causes of opportunistic and nosocomial fungal infections species such as Cladosporium, Mucor, Fusarium , Rhizopus and Pencillum , further cements the concept that cockroaches in hospitals a may be major public health concern and con rm the ndings of other studies conducted on domestic and hospital cockroaches (1)(2)(3)(4)(5)(6)(7)(8)(9) . What the study ndings indicate is that there needs to be more studies to be conducted to ascertain if medically important fungi on the surfaces of hospital cockroaches are etiological agents of HAIs including of newer fungal pathogens immunocompromised patients such as Talaromyces marneffei (29).…”
Section: Discussionsupporting
confidence: 53%
“…Kitchens and toilets are areas that are often contaminated with infectious microorganisms including bacteria, viruses, protozoa and fungi, as result it may not be unexpected that cockroaches may be reservoirs of infectious microorganisms. There have been a numbers of studies have suggested that hospital cockroaches may be potential carriers of infectious microorganisms including drug resistant bacteria (1)(2)(3)(4)(5)(6)(7)(8). Nevertheless there are limited studies that have looked in role of cockroaches as vectors and reservoirs of opportunistic and HAI associated with fungal pathogens (9) Hospital care associated infections (HAI) are a major public health concern worldwide because of the morbidity, mortality and cost associated with them (10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Cockroaches appear to be suitable mechanical transmitters for a wide range of food-borne pathogenic microorganisms due to their filthy behaviour and occurrence in places where food is stored or handled. 1,2 Microorganisms may be carried externally on the cuticle of cockroaches, 3,4 or may be ingested and then later excreted or regurgitated. 3,4 In this way, cockroaches can easily contaminate food when they come into contact with it.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Microorganisms may be carried externally on the cuticle of cockroaches, 3,4 or may be ingested and then later excreted or regurgitated. 3,4 In this way, cockroaches can easily contaminate food when they come into contact with it. Although there exist about 4000 species of cockroaches, only 30 are associated with human habitations.…”
Section: Introductionmentioning
confidence: 99%
“…The causes of foodborne illnesses are pathogens like bacteria, viruses, parasites, and chemical substances that enter the human body through contaminated food or water 2,3 . One of the potential vectors which can contaminate food is cockroaches, cause they are common in many human habitations, particularly in places where food stored or handled 4 .…”
Section: Introductionmentioning
confidence: 99%